Edukasi Pola Hidup Bersih dan Sehat Pada Lansia Untuk Meningkatkan Kualitas Hidup Lansia Di Dusun Landeuh Desa Sadananya Kecamatan Ciamis Jawa Barat - Endrian Mulyady Justitia Waluyo; Riska Ayu Nur Azizah; Lenna Mahdalena (LPPM STIKes Muhammadiyah Ciamis, 2024)
Introduction: The elderly population in Indonesia in the next few years will increase. The proportion of elderly people is estimated to be ten percent of the total population. The screening results show that the Ciamis area, especially Sadana, has a significant elderly population and experiences problems where the elderly still smoke, then in Landeuh hamlet there are other problems such as septic tank ownership and waste management. Objective:This community service aims to increase the knowledge of the elderly regarding the dangerous impacts of smoking, the impact of waste, and the impact of septic tanks. Method: This community service uses community nursing screening in Landeuh Sadananya hamlet, Ciamis Regency. The results of the screening netted 70 people. Counseling was carried out for the elderly, 56 people attended. The outreach media uses leaflets. Result: Shows an increase in knowledge, the average pre-test result is 47.8 while the post-test is 78 Conclusion: Leaflet media can be used for health education to effectively increase knowledge in the elderly